Illustration with the Emotion of Grief and Regret in Poems of Siavash Kasraei - mohammadamin ehsani estahbanati; Manijeh Abdollahi (مطالعات زبانی و بلاغی)
The art begins with an overwhelming feeling and affection on the soul of the artist and makes him create, create and create an artwork. This reaction, which is the result of the spiritual experiences of the artist, is one of the main elements and motivators in the compilation. One of the most important features of man is affection. This feature explains and points out the attitude of the human person, including the artist, to the phenomena and concepts of existence. The affection in the realm of artistic creation is how the artist interacts with the phenomena of the outside world. The main manifestations of affection are happiness, sorrow, love, hatred, despair, hope and regret. The sadness of emotion has always had a special place in poetry of our poets. The emotion of sorrow and regret is to correct the human nostalgia and regret of the past and the things that have been lost in the present. The purpose of this article is to investigate the emotion of regret and sadness and its role and place in the collection of Siavash Kasraei poems, which has been dealt with by descriptive-analytical method. The results of this research show that the emotion of regret and grief in the chess poetic manifestation is significant and can be considered as the reasons for the survival of his poem, kasraei’s regret can be divided into two categories of personal grief and social regret in the decoration of the word and its aesthetic elements, including poetry, ava, weight, vocabulary and division.